2002
DOI: 10.1103/physrevd.65.052006
|View full text |Cite
|
Sign up to set email alerts
|

Searches for new physics in events with a photon andb-quark jet at CDF

Abstract: T. AFFOLDER et al.PHYSICAL REVIEW D 65 052006 052006-2We have searched for evidence of physics beyond the standard model in events that include an energetic photon and an energetic b-quark jet, produced in 85 pb Ϫ1 of p p collisions at 1.8 TeV at the Tevatron Collider at Fermilab. This signature, containing at least one gauge boson and a third-generation quark, could arise in the production and decay of a pair of new particles, such as those predicted by supersymmetry, leading to a production rate exceeding st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(101 citation statements)
references
References 37 publications
11
90
0
Order By: Relevance
“…In particular, the rise of N ⊥ with p t (jet) to a saturation value (pedestal) should reflect increase of the MPI rate with increasing p-p centrality in response to the trigger condition [1,11]. Figure 2 (first) shows CDF UE data for N ⊥ vs p t (jet) (points) in a conventional plot format [12]. The curves are from PYTHIA.…”
Section: Pythia and The Underlying Event -Uementioning
confidence: 99%
“…In particular, the rise of N ⊥ with p t (jet) to a saturation value (pedestal) should reflect increase of the MPI rate with increasing p-p centrality in response to the trigger condition [1,11]. Figure 2 (first) shows CDF UE data for N ⊥ vs p t (jet) (points) in a conventional plot format [12]. The curves are from PYTHIA.…”
Section: Pythia and The Underlying Event -Uementioning
confidence: 99%
“…The UE for high-energy p-p collisions is by definition complementary to an eventwise-triggered dijet or pQCD leading-order process [51]. Access to the UE is expected via the transverse (azimuth) region or TR component of the single-particle charge density relative to the trigger (or of 1D azimuth correlations as in Fig.…”
Section: Underlying Event Vs Mb Dijetsmentioning
confidence: 99%
“…The UE study reported in Ref. [51] considers chargejet evolution and properties of the UE within an acceptance p t > 0.5 GeV/c and |η| < 1. Trigger (leading) jets (jet in each event with greatest P T 1 = i∈jet p ti ) fall in the range P T 1 ∈ [0.5, 50] GeV/c.…”
Section: A Conventional Underlying-event Analysismentioning
confidence: 99%
“…So, the practical understanding of UE is limited to the phenomenological models. The CDF [2][3][4][5] experiment at Tevatron and the ATLAS [6][7][8][9][10][11], ALICE [12] and CMS [13][14][15][16][17] experiments at LHC have carried out several measurements of parameters and observables sensitive to UE at their available center-of-mass energies ( √ s). Due to easy identification of Z-boson production, the experiments usually study the UE activities in the events containing the Drell-Yan(DY) process.…”
Section: Introductionmentioning
confidence: 99%